Pengaruh Return on Equity, Debt to Equity Ratio, Price to Earning Ratio dan Price to Book Value terhadap Return Saham - Yudistirha, Desy; Pontoh, Grace T.; Arif, Hermita (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Investors use financial ratio analysis to understand a company's financial condition. This study aims to analyze the impact of the Return On Equity Ratio (ROE), Debt To Equity Ratio (DER), Price To Earnings Ratio (PER), and Price To Book Value (PBV) on stock returns.The population of this study consists of consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2022-2023, totaling 76 companies. The sampling technique used is purposive sampling, resulting in a sample of 58 companies. The analytical method used is multiple linear regression analysis. The results of the study indicate that partially, ROE and PER have a positive and significant effect on stock returns. Conversely, DER and PBV do not have a partial effect on stock returns. This indicates that ROE and PER must be considered by both investors and companies as they are crucial indicators in evaluating the potential return on stocks.